2021
DOI: 10.3390/vaccines9091039
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin as Immune Potentiator for Enhancing Subunit Vaccine Efficacy against Bovine Viral Diarrhea Virus

Abstract: Bovine viral diarrhea virus (BVDV) is a pathogen associated with substantial economic losses in the dairy cattle industry. Currently, there are no effective vaccines against BVDV. Melatonin (MT) has been shown to have anti-inflammatory and anti-viral properties, and the use of MF59 in vaccines significantly enhances vaccine efficiency. Here, MT and MF59 were added into the Erns-LTB vaccine. Subsequently, their inhibitory activity on the NF-κB signaling pathway in Mardin-Darby Bovine Kidney cells and the hippoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Various reports have revealed the part played by antioxidants in ameliorating the adverse effects of vaccines, in addition to their significant role in disease management, especially those mediated by ROS such as toxoplasmosis [ 38 ]. Among these, RA has gained particular interest as a natural element with known antioxidant effects as well as immunomodulatory effects [ 39 , 40 ]. Thus, this study experimentally investigated the prospective role of nano-encapsulated RA as a novel adjuvant to boost the anti- Toxoplasma vaccine’s protective immunity, hand in hand with their ability to modulate the pathology imposed by parasitic infection as a natural antioxidant and anti-inflammatory agent.…”
Section: Discussionmentioning
confidence: 99%
“…Various reports have revealed the part played by antioxidants in ameliorating the adverse effects of vaccines, in addition to their significant role in disease management, especially those mediated by ROS such as toxoplasmosis [ 38 ]. Among these, RA has gained particular interest as a natural element with known antioxidant effects as well as immunomodulatory effects [ 39 , 40 ]. Thus, this study experimentally investigated the prospective role of nano-encapsulated RA as a novel adjuvant to boost the anti- Toxoplasma vaccine’s protective immunity, hand in hand with their ability to modulate the pathology imposed by parasitic infection as a natural antioxidant and anti-inflammatory agent.…”
Section: Discussionmentioning
confidence: 99%
“…Tryptophan is typically catabolized via three metabolic pathways: the kynurenine, the indole, and the serotonin pathways. While the kynurenine (Fiore and Murray, 2021; Gargaro et al, 2016; Moffett and Namboodiri, 2003; Proietti et al, 2020; Sorgdrager et al, 2019) and indole pathways (Gargaro et al, 2016; Rannug, 2022; Sadik et al, 2020; Zhang et al, 2020c) typically induce anti-inflammatory and immunosuppressive effects, the serotonin pathway produces melatonin, known as an immune booster (Calvo et al, 2013; Carrillo-Vico et al, 2013) and a vaccine-adjuvant (Wang et al, 2021; Zhang et al, 2020a). Tryptophan metabolism was detected in both the LmCen -/- and the LmWT datasets, however, analysis of the metabolites showed that tryptophan metabolism was differentially regulated in the immunized and infected conditions as revealed by the concentrations of kynurenine, indole-3-acetaldehyde and melatonin.…”
Section: Discussionmentioning
confidence: 99%
“…Upon its release, melatonin has been shown to induce a strong-pro-inflammatory response in the host by stimulating significant IL-12 release in dendritic cells and macrophages (Calvo et al, 2013; Cutolo et al, 1999; Lissoni, 1999). The immune-boosting properties of melatonin have led to its usage as a vaccine adjuvant (Wang et al, 2021; Zhang et al, 2020a). Thus, the elevated levels of melatonin observed in LmCen -/- immunization may have an endogenous adjuvant activity potentiating a strong its immune response though this remains to be tested experimentally.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, several MPXV antigen‐specific mRNA vaccines are being developed, presenting high effectiveness in triggering immune responses and protecting mice from vaccina virus challenge 52–57 . Moreover, based on MPXV specific protective proteins, our team also developed one subunit vaccine and two mRNA vaccine candidates, all of which showed promising results in inducing cellular and humoral immune responses, as well as anti‐vaccinia virus activity in mouse model 58,59 …”
Section: Vaccination Strategies Against Infection Of Mpxvmentioning
confidence: 99%